Impact of heavy metals in paddy field soil on human body / Nursuhaila Muhamad Fauzi ... [et al.] - Muhamad Fauzi, Nursuhaila; Mohd Nasir, Nur Azlin Atikah; Ramli, Nurul Annisa; Fadzil, Nur Farhan Natasha; Ramli, Rohayu; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Producers use increasing amounts of pesticides to safeguard their crops as the population grows and the demand for rice rises as a result. It is because of the metals' non-biodegradable characteristics and tendency to bioaccumulate in the environment, heavy metal contamination in paddy fields has so recently raised serious concerns as an environmental contaminant. Furthermore, heavy metals are categorised as significant hazardous substances because of their great potential damage to human health and the ecosystem. They have also been mentioned as possible contaminants in rice on a regular basis. Heavy metals come in two different types by nature which is organic and inorganic. Metallic elements with a density higher than that of water are referred to as heavy metals.